PERANCANGAN SISTEM INFORMASI PENGUKURAN KINERJA MITRA STATISTIK BERBASIS PENILAIAN 720 DERAJAT - Tri Hayuni Syardi (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2021)
The Central Statistics Agency (BPS-Statistics Indonesia) as a non-ministry government agency that organizes basic statistical activities upholds the quality of the data produced. In order to maintain the quality of the data, each component of statistical activities must meet the quality standards set. Ensuring data quality is not only about ensuring the quality of the methodology used but also on the officers deployed to carry out statistical ac-tivities. The lack of staff in implementing statistical activities makes BPS-Statistics Indonesia have to recruit statistical partners. In order for statistical partners to meet the quality standards set, so it is necessary to as-sess the performance of statistical partners. This paper presents a system design for statistical partner perfor-mance appraisal by applying the 720 degrees method. This method is able to accommodate the need for partner performance appraisal because the assessment is not only carried out by single person but many people have links to the partner in order to avoid subjectivity. The 720 degrees method also complements the 360 degrees assessment method by adding assessment feedback so that statistical partners can make improvements to their performance.